SISTEM INFORMASI MANAJEMEN EVENT UNTUK PENINGKATAN PRODUKTIVITAS BUDIDAYA IKAN BERBASIS WEBSITE PADA DINAS PERIKANAN DAN KELAUTAN KABUPATEN INDRAMAYU - Ahmad Lubis Ghozali; Darsih; Sri Dyah Wulandari (Journal of Informatics and Computing, 2022)
Fish farming is one of the sources of income for the people of Indramayu district which is currently widely occupied, it is not surprising that nowadays many people are flocking to cultivate fish. There are groups that cultivate including freshwater fish such as catfish, carp, and tilapia. There are also brackish water fish such as vaname shrimp, tiger shrimp, and milkfish. The fish cultivators in selling their harvests are still done conventionally, namely with the services of middlemen or collectors. This results in prices being often manipulated by collectors. One way to improve the sales system is to build an event management application in the field of fish harvest auctions. This application can be used as an alternative for cultivators for media promotion and cutting the marketing distribution chain. The benefits of this event management application are that cultivators get more competitive prices and can directly increase profits, while the benefits for buyers get cheaper prices. This web-based application, to provide information about an event or harvest auction that is managed online. This application is designed through the creation of flowcharts, UML, ERD, and mockups. Then it is implemented using the PHP programming language with the Laravel framework and the MySQL database management system